The Impact of Microbial Diversity on Biogenic Amines Formation in Grasshopper Sub Shrimp Paste During the Fermentation - Sang, Xue; Li, Kexin; Zhu, Yaolei; Ma, Xinxiu; Hao, Hongshun; Bi, Jingran; Zhang, Gongliang; Hou, Hongman (Frontiers in Microbiology, 2020)
Biogenic amines (BAs) and microbial diversity are important factors affecting food quality and safety in fermented foods. In this study, the bacterial and fungal diversity in grasshopper sub shrimp paste taken at different fermentation times were comprehensively analyzed, while the pH, colony counts, salinity, total volatile base nitrogen (TVB-N) and BA contents were quantitatively determined. In addition, the correlations among the samples with respect to microbial communities and the different parameters investigated especially BAs were also established. By combining the results of spearman correlation heatmap with the contents of BAs produced by the 102 halotolerant bacteria isolated from the grasshopper sub shrimp paste, six major genera of bacteria (Jeotgalibaca, Jeotgalicoccus, Lysinibacillus, Sporosarcina, Staphylococcus, and Psychrobacter) were found to be positively correlated with BA production level, suggesting that these bacteria might have a strong tendency to produce BAs. Other bacteria such as Lentibacillus, Pseudomonas, and Salinicoccus were considered as poor BA producers. The grasshopper sub shrimp paste was characterized by a relatively high abundance of Tetragenococcus, which was the dominant genus during the fermentation process, and it also produced a relatively high level of BAs but the spearman correlation heatmap revealed a negative correlation between T. muriaticus and BA level. Analysis of the species relevance network in grasshopper sub shrimp explained that the actual production of BAs by a certain strain was closely related to other species present in the complex fermentation system.